Far distance measurement of electric current through infrared radiation. (August 2022) - Ren, Chao; Bai, Libing; Liang, Yiping; Tian, Lulu; Zhang, Jie
Highlights: Establish a quantitative mathematical model of current and heat radiation based on Joule heat. Design a new radiant sensor for current measurement by analyzing the properties of different materials, and the sensitivity, structure and specific size are given. Realize a far-distance current measurement of power frequency AC, which provides a potential solution for safe current measurement in engineering. Abstract: Ohm's law and Electromagnetic Induction law are two fundamental laws used for the current measurement. However, these two methods require putting resistance into the circuit or magnetic sensor close to the line, which is dangerous when the wireline has high voltages. To improve the safety, this paper proposes a non-contact far distance current measurement method, which is in conjunction with a fuse-like radiant sensor made of metal foil and an infrared radiation (IR) camera, without any additional conjunction line. Nature behind that is a mathematical model based on another law, Joule Heating. The mathematical model unifies the alternating current (AC) and heat conduction equation in the dynamic process, quantitatively determines the relationship between the sinuous temperature variation and current amplitude along the wireline. Experiments verify that the proposed method can measure current with the relative error within ± 3.66 % in the range of 1.05–3.45Arms at power frequency (50 Hz) from 1 m away. Therefore, the proposed method has a bright future for electric current measurement of tour inspection, especially in high voltage transmission systems.